1998
DOI: 10.1303/jjaez.42.77
|View full text |Cite
|
Sign up to set email alerts
|

Ethological and Chemical Discrimination between Thelytokous and Arrhenotokous Thrips nigropilosus Uzel, with Discussion of Taxonomy.

Abstract: The mating behavior of Thrips nigropilosus, which consists of arrhenotokous and thelytokous populations, was studied under laboratory conditions. The variation in esterase isozymes of individual adult females from a thelytokous population and seven arrhenotokous populations was analyzed by polyacrylamide gel electrophoresis. Mating occurred between individuals of arrhenotokous populations from different localities. Although males of an arrhenotokous population approached and attempted to copulate with females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Among them, T. nigropilosus had a remarkably higher infestation frequency than other thrips species irrespective of collection period, island and cultivation environment. This result suggests that T. nigropilosus is an important pest species of chrysanthemum in Okinawa, which was unexpected considering that it has not been recognized as a pest of chrysanthemum in Okinawa (Nagamine 1994), although it was collected from an unidentified asteraceous plant on Okinawa Island in 1994 (Nakao & Yabu 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Among them, T. nigropilosus had a remarkably higher infestation frequency than other thrips species irrespective of collection period, island and cultivation environment. This result suggests that T. nigropilosus is an important pest species of chrysanthemum in Okinawa, which was unexpected considering that it has not been recognized as a pest of chrysanthemum in Okinawa (Nagamine 1994), although it was collected from an unidentified asteraceous plant on Okinawa Island in 1994 (Nakao & Yabu 1998).…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon was also observed between two reproductive forms of T. nigropilosus and suggested that they are a separate species (Nakao and Yabu, 1998). To discuss the taxonomical relationship between two reproductive forms of T. tabaci, it is necessary to investigate their reproductive isolation in detail.…”
Section: Discussionmentioning
confidence: 97%
“…Murai (1990) found that these two reproductive types are distinguishable by esterase zymogram. Nakao and Yabu (1998) suggested that thelytokous and arrhenotokous Thrips nigropilosus correspond to separate species, due to the existence of apparent genetic differences and reproductive isolation; however, the phylogenetic relationship between the two reproductive forms of T. tabaci is unclear, and their taxonomical relationship remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that although arrhenotokous males attempted to copulate with thelytokous females, the males were rejected, suggesting the existence of reproductive isolation (TODA & MURAI 2007). The same behaviour between thelytokous females and arrhenotokous males was reported in the Thrips nigropilosus UZEL, 1895 species complex (NAKAO & YABU 1998). Reproductive isolation seems to be a logical key factor in the divergence of the L1 and L2 forms; this reproductive isolation requires detailed investigation, however.…”
Section: Speciation In Trhrips Tabacimentioning
confidence: 77%